MINERALOGICAL AND GEOCHEMICAL FEATURES AND PROSPECTS FOR COMPLEX MINERALIZATION OF THE YAKHTON DEPOSIT (MOUNTAINS CHAKYL-KALYAN, UZBEKISTAN) - Sardor S. Sayitov; Vladimir D. Tsoi (Известия Томского политехнического университета: Инжиниринг георесурсов, 2023)
Link for citation: Sayitov S.S., Tsoi V.D. Mineralogical and geochemical features and prospects for complex mineralization of the Yakhton deposit (mountains Chakyl-Kalyan, Uzbekistan). Bulletin of the Tomsk Polytechnic University. Geo Аssets Engineering, 2023, vol. 334, no. 9, рр. 76-90. In Rus.